2020
DOI: 10.1021/acs.jafc.9b07494
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Decatrienones with a Pineapple-like Aroma from 1-13C-Acetate by Cell Cultures of the Birch Polypore, Fomitopsis betulina

Abstract: During submerged cultivation, the edible basidiomycete Fomitopsis betulina (previously Piptoporus betulinus) developed a fruity odor, strongly reminding of pineapple. Olfactometric analysis showed that this impression was mainly caused by the two (5E/Z,7E,9)-decatrien-2-ones. At the time of maximum concentration on the 5th day, the (5E/5Z)-ratio was 94:6. Three hypotheses were experimentally examined to shed light onto the genesis of the uncommon volatiles: first, an indirect effect of agro-industrial side-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Likewise unusual were dodec-11-enoic acid and di-and tri-unsaturated C16 isomer fatty acids in the lipids of Flammulina velutipes [112]. An excellent proof of the enormous synthetic potential of basidiomycetes was the identification of the (5E/Z,7E,9)-decatrien-2-ones in submerged, cultured Fomitopsis betulina (Figure 5b) [110,111]. The (5Z)-isomer possessed a strong pineapple flavour and belongs to the most potent flavour compounds known.…”
Section: Formation Of Volatile Flavoursmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise unusual were dodec-11-enoic acid and di-and tri-unsaturated C16 isomer fatty acids in the lipids of Flammulina velutipes [112]. An excellent proof of the enormous synthetic potential of basidiomycetes was the identification of the (5E/Z,7E,9)-decatrien-2-ones in submerged, cultured Fomitopsis betulina (Figure 5b) [110,111]. The (5Z)-isomer possessed a strong pineapple flavour and belongs to the most potent flavour compounds known.…”
Section: Formation Of Volatile Flavoursmentioning
confidence: 96%
“…The combined action of a DyP and a laccase from Funalia trogii resulted in a complete conversion of (+)-valencene within 24 h (Figure 5a). An excellent proof of the enormous synthetic potential of basidiomycetes was the identification of the (5E/Z,7E,9)-decatrien-2-ones in submerged, cultured Fomitopsis betulina (Figure 5b) [110,111]. The (5Z)-isomer possessed a strong pineapple flavour and belongs to the most potent flavour compounds known.…”
Section: Formation Of Volatile Flavoursmentioning
confidence: 99%
“…Thus, the fungal strain was able to biotransform food by-products into pleasant mixtures of complex flavors [12]. Grosse et al [116] used cabbage cuttings as a substrate in a fermentation medium submerged with the edible basidiomycete Fomitopsis betulina. They reported that the fermented product presented a fruity odor, strongly reminiscent of pineapple.…”
Section: Fermentation With Basidiomycetes Using Agro-industrial Resid...mentioning
confidence: 99%
“…They reported that the fermented product presented a fruity odor, strongly reminiscent of pineapple. The olfactory analysis showed that this impression was mainly caused by the two (5E/Z,7E,9)-decatrien-2-one compounds [116,121].…”
Section: Fermentation With Basidiomycetes Using Agro-industrial Resid...mentioning
confidence: 99%
“…Main cultures were extracted by sequential stir bar sorptive extraction (SBSE) using Twisters (10 mm × 0.5 mm, Gerstel, Mülheim, Germany) coated with polydimethylsiloxane (PDMS) as described elsewhere (Grosse et al 2020;Sampedro et al 2009). In brief, 5 mL of the respective broth were extracted for 1 h at room temperature.…”
Section: Volatile Analysismentioning
confidence: 99%